Three essays on the relationship between financial worry and financial behaviors - Brandon-Joseph, Lamindy (Kansas State University, 2023)
Despite our intuitive appreciation of the power and influence of emotions, gaps remain in what we understand of its relationship with behaviors within the personal finance domain. Financial worry is the emotion of interest for this research. This dissertation uses three studies to investigate the potential relationship between financial behaviors and two specific types of financial worry—investment and retirement worry. Each study relies on a distinct theoretical perspective which allowed for testing these emotions as either predictor or outcome variables. Essay one used the information source framework (Beales et al., 1981) combined with the information search process model (Kuhlthau et al., 2008) as theoretical support for investigating the association between investment worry and sources chosen for financial information. The combined 2018 National Financial Capability Study (NFCS) State-by-State (NFCS-SS) and Investor Surveys (NFCS-IS) provided the data. Results from the path analysis found no significant direct paths from investment worry to external information sources. Furthermore, the study did not find statistical support for objective financial knowledge mediating the relationship between investment worry and any of the external information sources. Essay two relied on the transactional theory of stress and coping model (Lazarus & Folkman, 1984) to explore the relationship between avoidance behaviors and retirement worry. The 2021 NFCS-SS provided the data for this study. Results from the OLS model provided evidence of an inverse relationship between avoidance behaviors and retirement worry. A multinomial regression model was then used to examine the level of retirement worry relative to avoidance behavior. Findings showed that, in general, avoidance behavior is negatively related to the level of retirement worry. Essay three utilized prospect theory (Kahneman & Tversky, 1979) to predict the relationship between retirement worry and investment risk behavior. The combined 2018 NFCS-SS and NFCS-IS provided the data for this study. Results from the multinomial regression model showed the strongly disagree category of retirement worry relative to those who are neutral had a positive relationship with holding more than half of an investment portfolio in stock relative to those holding no stock. There were no significant relationships found between any category of retirement worry and the less than half category of stock ownership when compared to owning no stocks. The relationship between any level of retirement worry and the more than half category of stock ownership, relative to the less than half category, was also not significant when all other variables were held constant. Overall, findings support increased attention to financial worries—specifically investment and retirement worry, as emotional factors that can influence the financial planning process. Financial professionals can use these insights when preparing to deliver financial information to clients, when helping clients manage their coping strategies, or when making financial recommendations. Future research can also expand our understanding of other mechanisms that may mitigate the influence of these emotions on financial outcomes.
Keywords: Investment worry; Retirement worry; Financial information sources; Avoidance behaviors; Loss aversion